2018
DOI: 10.1002/cphc.201800723
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Nb2O5 Lewis Acid Catalysis for Activation of Carboxylic Acids in the Presence of a Hard Base

Abstract: The Nb2O5 surface catalyzes the amidation of carboxylic acids with amines through Nb5+ Lewis acid activation of the C=O group. In this work, DFT calculations were applied to theoretically investigate the C=O bond activation of a model carboxylic acid (acetic acid) on θ‐Al2O3(110), anatase TiO2(101), and T‐Nb2O5(100) surfaces. The adsorption sites, adsorption energies, reaction energy barriers, electronic properties, and vibrational frequency of acetic acid were examined in detail. It was found that the bond ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 44 publications
4
22
0
Order By: Relevance
“…revealed Mo improved the adsorption energy of AcOH dramatically compared with the adsorption onto non-metal loading CNTs, confirming the binding promotion effect of Mo to the AcOH adsorption, in line with recent study [5]. Over Mo/N p -CNT, AcOH exhibited higher binding energy, ascribed to the unpaired electron of pyridinic N acts as electron acceptor (Lewis acid), such that reinforces the binding between the catalyst and adsorbate molecule [34]. This is also confirmed by the lower adsorption energy of AcOH molecule over Mo/CNT.…”
Section: Results and Discussion 21 Catalyst Designsupporting
confidence: 86%
“…revealed Mo improved the adsorption energy of AcOH dramatically compared with the adsorption onto non-metal loading CNTs, confirming the binding promotion effect of Mo to the AcOH adsorption, in line with recent study [5]. Over Mo/N p -CNT, AcOH exhibited higher binding energy, ascribed to the unpaired electron of pyridinic N acts as electron acceptor (Lewis acid), such that reinforces the binding between the catalyst and adsorbate molecule [34]. This is also confirmed by the lower adsorption energy of AcOH molecule over Mo/CNT.…”
Section: Results and Discussion 21 Catalyst Designsupporting
confidence: 86%
“…In order to further support these experimental observations, DFT calculations were employed to theoretically investigate the C=O bond activation of a model carboxylic acid (acetic acid) on the T-Nb 2 O 5 (100) surface. [91] The bulk structure of T-Nb 2 O 5 as well as its surface structure, T-Nb 2 O 5 (100), which should have the lowest surface energy, are shown in Figure 5. [20] For Table 3.…”
Section: Water and Base Tolerance Of Nb 2 Omentioning
confidence: 99%
“…In these works, we demonstrated that the reactivity is controlled in delicate energetics and by some predominant factors. For example, the reactivity is correlated to the d ‐band center of each metal atom and the perimeter site, i. e. interface between NC and support, is relevant as the catalytic center ,. We also systematically investigated the geometric structure and bond activation of bimetallic Cu−M (M: group 8–11 metals) NC; in particular, the catalytic activity of Cu−Rh NC .…”
Section: Introductionmentioning
confidence: 99%
“…For example, the reactivity is correlated to the d-band center of each metal atom and the perimeter site, i. e. interface between NC and support, is relevant as the catalytic center. [44,46] We also systematically investigated the geometric structure and bond activation of bimetallic CuÀM (M: group 8-11 metals) NC; [47] in particular, the catalytic activity of CuÀRh NC. [48] Through these systematic studies on NC catalysts, we have clarified some important aspects of the NC catalysts.…”
Section: Introductionmentioning
confidence: 99%